Influence of Drought Mitigation Strategies on Food Security: A Case of Laikipia East, Laikipia County, Kenya - Muhua, George O.; Waweru, John K. (European Scientific Journal, ESJ, 2017)
Achieving food security in the Kenyan ASALs during droughts is a constant challenge. Reactive approaches to drought-risk management have been ineffective and poorly coordinated leading to vulnerability of households to food insecurity despite adoption of Hyogo Framework of Action 2005-2015 (HFA). HFA recommends continuous systematic planning and management of drought risk, as it should be anticipated and planned for, in its manifest phases of normalcy, early stage, alert and emergency periods each with specific mitigation activities. The study with special reference to Laikipia East Sub-County revealed that majority of households were aware of drought mitigation strategies which influenced household food security but these were poorly coordinated, late, insufficient and lacked sufficient funding. The study also found out that household participation was low in implementation. The study recommends more capacity building on drought mitigation strategies, timely planning for drought to ensure coordinated response to drought especially in human and livestock relief projects. Finally the study recommends involvement of technical field officials and local leaders as they are better placed to identify working strategies and rightful targeting.